2020
DOI: 10.3389/fphar.2020.01078
|View full text |Cite
|
Sign up to set email alerts
|

Mu Opioid Receptor Heterodimers Emerge as Novel Therapeutic Targets: Recent Progress and Future Perspective

Abstract: Opioids are the most effective analgesics used in the clinical management of cancer pain or non-cancer pain. However, chronic opioids therapy can cause many side effects including respiratory depression, nausea, sedation, itch, constipation, analgesic tolerance, hyperalgesia, high addictive potential, and abuse liability. Opioids exert their effects through binding to the opioid receptors belonging to the G-protein coupled receptors (GPCRs) family, including mu opioid receptor (MOR), delta opioid receptor (DOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 78 publications
(115 reference statements)
1
61
0
1
Order By: Relevance
“…We subsequently explored that possible role of opioid receptors in low-dose formalin-induced itch in mice. Opioid receptors can be divided into three classes: μ-, κ-, and δ-opioid receptors, which are distributed in the central nervous system (CNS) and peripheral nervous system (PNS) ( 39 ). It has been reported that μ-opioid receptor agonists evoke itch, while κ-opioid receptor agonists inhibit itch in both animal models and human ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…We subsequently explored that possible role of opioid receptors in low-dose formalin-induced itch in mice. Opioid receptors can be divided into three classes: μ-, κ-, and δ-opioid receptors, which are distributed in the central nervous system (CNS) and peripheral nervous system (PNS) ( 39 ). It has been reported that μ-opioid receptor agonists evoke itch, while κ-opioid receptor agonists inhibit itch in both animal models and human ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…Opioids have their side-effects and development of targeted opioid drugs for Mu receptor heterodimers is an opportunity for research in times to come. [ 37 ]…”
Section: Pandemic Woesmentioning
confidence: 99%
“…Gαq subunit activates phospholipase C to produce inositol trisphosphate and diacylglycerol for the phosphorylation of protein kinase C (PKC) [ 22 , 23 ]. Gαi/o subunit inhibits the adenylate cyclase for producing cyclic adenosine monophosphate, which inactivates protein kinase A (PKA) [ 23 , 25 ]. Morphine and DAMGO further mediate MAPKs activation that has been directly verified by the use of its signaling inhibitors, such as PKC or PKA inhibitors, in MOR-dependent signaling [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, mechanisms of receptor interactions between OR and OR/other classes of GPCRs give the hypothesis of cross-talk that occurs in heterodimer formation, heterologous desensitization and intracellular signaling [ 24 , 25 , 26 , 27 , 28 , 29 ]. For example, CYM51010, a MOR-DOR-biased agonist, increases co-expression of MOR and DOR in injured DRG neurons and has analgesic effects on neuropathic pain by subcutaneous administration [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%